RESPONSE TO HOME LEARNING SYSTEM POLICY IN LEARNING INDONESIAN LANGUAGE - Risna Rosida; Teti Sobari; Ika Mustika (IKIP Siliwangi, 2022)
The emergence of the Covid 19 outbreak has affected various sectors in the world, including in Indonesia. The world of education is one of the areas affected by this outbreak. All levels of education from PAUD to tertiary institutions must implement the Home Learning System (BDR). Various obstacles arise with the implementation of this policy. The purpose of this study was to analyze the problems faced by teachers and students when implementing BDR policies. The method used in this research is interview and survey to describe social phenomena that occur through data in the form of diagrams taken from several students' questionnaires and teacher interviews. The results showed that the problems faced by students were difficulties in understanding lessons and network constraints that were also experienced by the teacher. It can be concluded that online learning must continue to be implemented, regardless of the existing obstacles, so that there is no lost learner generation. In the world of education, in this case, the teacher must innovate so that the effectiveness of learning can be achieved.